Betrayal or Blasphemy? "Handing over" God's Agent in the Portrayals of Judas in the Gospels. (November 2019) - King, Fergus J.
The exact identification of Judas Iscariot has long vexed scholars. The gospel accounts themselves say little, offering a variety of possible motivations for his action, including money and Satanic impulse. The key word used of Judas' actions, paradidona i, found in all four canonical Gospels, offers two translations, "hand over" and "betray, " which remain highly contested. However, the fact that both God and people may "hand over" offers a possible solution, which emerges from an examination of the genre and environment of the four Gospels.